The Development of the 'Farmer's Mansion' in Kansas: A Regional Case Study of Vernacular Architecture, 1850 - 1900 - Cantril, Matt (Kansas State University, The Chapman Center for Rural Studies, 2013)
This study includes maps of the country, information from books and online articles as well as photographs and diagrams of homes. The I-House was an early form of architecture throughout the History of the United States. This home migrated with the North Midland group.
Matt Cantril, “The Development of the 'Farmer's Mansion' in Kansas: A Regional Case Study of Vernacular Architecture, 1850 - 1900,” Chapman Center Research Collections, accessed November 13, 2020, https://ccrsresearchcollections.omeka.net/items/show/227.
Keywords: "farmers" mansion; Fred Kniffer; I-house; Midwest; Vernacular Architecture; North Midlanders